Entrepreneurial potential and agribusiness desirability among youths in South Kivu, Democratic Republic of the Congo - Simbeko, G.; Dontsop Nguezet, Paul M.; Sekabira, H.; Yami, M.; Amato-Masirika, S.; Bheenick, K.; Bugandwa, D.; Nyamuhirwa, D.A.; Mignouna, J.; Bamba, Z.; Manyong, Victor (MDPI, 2023)
In the Democratic Republic of Congo (DRC), entrepreneurship in the agriculture sector remains for youth a key pillar for income creation. However, few are attracted by agribusiness despite stakeholders’ efforts toward engaging youth in agriculture. Therefore, this study examines the relationship between entrepreneurial potential characteristics and youth desirability to start an enterprise in agriculture among 514 young people in Eastern DRC. This study revealed that youth in South Kivu have different entrepreneurship potential features and agribusiness desirability levels according to their gender and living area. Hence, the youth’s agribusiness desirability is motivated by an awareness of emerging agripreneurial activities, land ownership, parent involvement in farming activities as a role model, perceived agribusiness as an employment source, management-organizing and opportunistic competencies, market analysis, negotiating, and planning skills. Therefore, efforts to attract youth into agribusiness should focus on the use of media, the creation of awareness of available agribusiness initiatives in their area, and the setup of land policy. This is in addition to putting in place capacity-building programs on entrepreneurial and business skills through incubators, and the formalization of youth agribusiness groups that foster capitalizing experiences between new and accelerated agripreneurial enterprises, with the support of parents and financial institutions, focusing on gender sensitivity, in both rural and urban areas.